Plant lignans inhibit growth and trichothecene biosynthesis in Fusarium graminearum. (9th April 2014) - Kulik, T.; Buśko, M.; Pszczółkowska, A.; Perkowski, J.; Okorski, A.
Abstract Lignans are a group of diphenolic compounds with anticancer and antioxidant properties which are present in various grains, although their effect on toxigenic fungi has been poorly examined to date. In this study, the impact of the plant lignans pinoresinol and secoisolariciresinol on growth and trichothecene biosynthesis by five Fusarium graminearum strains of different chemotypes was examined in vitro. Both tested lignans exhibited radial growth inhibition against the fungal strains. RT‐qPCR analyses of tri4, tri5 and tri11 genes encoding the first steps of the trichothecene biosynthesis pathway revealed a decrease in tri mRNA levels in lignan‐treated fungal cultures. Correspondingly, decreased accumulation of toxins in lignan‐treated cultures was confirmed by GC‐MS analysis. This is the first study to demonstrate the inhibitory effect of both pinoresinol and secoisolariciresinol on growth and trichothecene biosynthesis in F. graminearum. Significance and Impact of the Study Knowledge of the regulation of trichothecene production in Fusarium graminearum by environmental cues is key to the design of novel strategies to reduce mycotoxin levels in grains. Here, we show that the lignans pinoresinol and secoisolariciresinol, which occur in wheat grains, inhibit radial growth and decrease trichothecene levels in five F. graminearum strains. RT‐qPCR analysis reveals that the reduction in trichothecene level in lignan‐treated fungal cultures is associated with decreased mRNA transcript levels for the tri4, tri5 and tri11 genes that are involved in the trichothecene biosynthesis pathway.